Regional Economic Outlook, April 2019, Sub-Saharan Africa : Recovery Amid Elevated Uncertainty. (International Monetary Fund, 2019)
The economic recovery in sub-Saharan Africa is expected to continue, but at a slower pace than envisaged in October 2018. This weaker outlook reflects domestic and external challenges. On the external side, the global expansion is losing momentum, including in China and the euro area, trade tensions remain elevated, global financial conditions have tightened, and commodity prices are expected to remain low. On the domestic front, security challenges, climate shocks, and policy uncertainty are hampering investment and weighing on economic prospects in several countries. Under current policies, medium-term average growth for the region is expected to continue to fall well short of what is needed to absorb the new entrants to the labor force and to deliver limited gains in living standards.